2009
DOI: 10.1111/j.1464-410x.2008.08329.x
|View full text |Cite
|
Sign up to set email alerts
|

A double‐blind randomized controlled trial of electromagnetic stimulation of the pelvic floor vs sham therapy in the treatment of women with stress urinary incontinence

Abstract: OBJECTIVE To compare the efficacy of extracorporeal electromagnetic stimulation (ES) of the pelvic floor for treating stress urinary incontinence (SUI) vs sham ES. PATIENTS AND METHODS In all, 70 women with urodynamically confirmed SUI were randomized to receive active (35) or sham (35) ES. The NeoControl chair (NeoTonus, Marietta, GA, USA) was used, and treatment consisted of three sessions per week for 6 weeks. data were collected before and after treatment on all women, including a 20‐min provocative pad‐te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0
7

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(86 citation statements)
references
References 20 publications
0
69
0
7
Order By: Relevance
“…Gilling et al 4 described the use of this technique to stimulate S-3 nerve roots bilaterally via their sacral foramina to reduce idiopathic bladder hyperactivity. However, no study has determined the functional variability of sacral roots.…”
Section: Discussionmentioning
confidence: 99%
“…Gilling et al 4 described the use of this technique to stimulate S-3 nerve roots bilaterally via their sacral foramina to reduce idiopathic bladder hyperactivity. However, no study has determined the functional variability of sacral roots.…”
Section: Discussionmentioning
confidence: 99%
“…Several early uncontrolled trials reported efficacy in urinary incontinence treatment, with improvement rates from 35% to 70%, 21,22 whereas in controlled trials the results were conflicting 14,23 and no additional benefit over PFMT was demonstrated. 24,25 The lack of evidence is compounded by differences in stimulation parameters and duration of treatment. Women with SUI who are having difficulties to correctly perform PFMT may benefit from a device which directly stimulates contraction of the pelvic floor.…”
Section: Electrical Stimulationmentioning
confidence: 99%
“…Nie można pominąć treningu skupionego na długiej kontrakcji mięśni (stymulacja włó-kien S). Wykazano, że stymulacja mięśni dna miednicy zwiększa liczbę włókien mięśniowych typu S w okolicy okołocewkowej [29,30]. Nie zaleca się stosowania elektrostymulacji u pacjentów zdolnych do wolicjonalnego skurczu mięśni dna miednicy [6].…”
Section: Elektrostymulacjaunclassified